2020
DOI: 10.4028/www.scientific.net/jnanor.61.32
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Crystalline Phase Formation in Titanium-Based Bimetallic Clusters

Abstract: In this work, we simulated and analysed phase transformations in the structure of nanosized bimetallic titanium-containing clusters during the cooling process. The results demonstrate the predominantly α+β crystalline structure of the TiAl nanoalloy after cooling, and the TiV nanoalloy has an amorphous structure. The glass transition temperatures for bimetallic systems TiAl and TiV for various compositions were determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
1
0
1
Order By: Relevance
“…Кроме того, эти зонные структуры могут возникать не только в области образования манжеты, но также в областях, содержащих в основном определенный сорт атомов металла. В дальнейшем изучение температурных зависимостей изменения фазового состава биметаллических нанокластеров распространено нами на другие биметаллические системы [26].…”
Section: результаты и обсуждениеunclassified
“…Кроме того, эти зонные структуры могут возникать не только в области образования манжеты, но также в областях, содержащих в основном определенный сорт атомов металла. В дальнейшем изучение температурных зависимостей изменения фазового состава биметаллических нанокластеров распространено нами на другие биметаллические системы [26].…”
Section: результаты и обсуждениеunclassified
“…Hence, an appropriate fabrication method to produce Ti–Ag-based alloys with fine Ag phases not only in binary alloy systems but also in multicomponent alloys is desired [ 41 ]. It has been reported that Ti-based alloys, including ternary alloys [ 42 , 43 , 44 ], show particular structural changes during mechanical alloying and cooling in nanoscale alloys. The successful fabrication of ternary and/or multicomponent Ti–Ag-based alloys containing fine Ag particles with LPS may offer a unique opportunity for the development of Ti–Ag-based dental and antibacterial materials.…”
Section: Introductionmentioning
confidence: 99%